Islam and Muslim Life in West Africa : Practices, Trajectories and Influences. - Sounaye, Abdoulaye. (ZMO-Studien Series, 2022)
The refereed series ZMO-Studien publishes monographs and edited volumes which mirror the interdisciplinary research programme and approach of the Leibniz-Zentrum Moderner Orient.